2019
DOI: 10.1007/s42690-019-00066-x
|View full text |Cite
|
Sign up to set email alerts
|

Watermelon-infesting Tephritidae fruit fly guild and parasitism by Psyttalia phaeostigma (Hymenoptera: Braconidae)

Abstract: An ecological guild of Tephritidae fruit flies exploits cucurbit vegetable fruits, tremendously reducing their production worldwide. Knowledge of the composition of the guild of infesting flies in the field and information on their natural enemy species, might improve pest management strategies. Our aim was therefore to identify Tephritidae species infesting the watermelon Citrullus lanatus (Thunb.) Matsum. & Nakai in the Republic of Benin. Morphological and molecular identification of parasitoid species prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Fruit flies represent the most notorious pests of economic importance on cucurbit. , They are responsible of damaging large quantities of fruits and vegetables grown in the tropics. ,, The most prominent and common fruit fly species infesting cucurbit fruit in Sub-Saharan Africa especially watermelon are D. acus vertebratus (Bezzi), D. bivittatus (Bigot), D. punctatifrons (Karsch), D. frontalis (Becker), D. lounsburyii (Coquillet), D. ciliatus (Loew) and Zeugodacus cucurbitae ( Coquillett). In Benin, D. vertebratus is reported as the most dominant species and causes up to 80% yield losses . A recent study in ref in Southern Benin also revealed that D. vertebratus was the predominant species constituting 65% of the 17,665 Tephritid adults observed. Zeugodacus cucurbitae prefers watermelon, pumpkin and cucumber and can cause up to 100% loss in an unprotected crop .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Fruit flies represent the most notorious pests of economic importance on cucurbit. , They are responsible of damaging large quantities of fruits and vegetables grown in the tropics. ,, The most prominent and common fruit fly species infesting cucurbit fruit in Sub-Saharan Africa especially watermelon are D. acus vertebratus (Bezzi), D. bivittatus (Bigot), D. punctatifrons (Karsch), D. frontalis (Becker), D. lounsburyii (Coquillet), D. ciliatus (Loew) and Zeugodacus cucurbitae ( Coquillett). In Benin, D. vertebratus is reported as the most dominant species and causes up to 80% yield losses . A recent study in ref in Southern Benin also revealed that D. vertebratus was the predominant species constituting 65% of the 17,665 Tephritid adults observed. Zeugodacus cucurbitae prefers watermelon, pumpkin and cucumber and can cause up to 100% loss in an unprotected crop .…”
Section: Introductionmentioning
confidence: 82%
“…13−17 In Benin, D. vertebratus is reported as the most dominant species and causes up to 80% yield losses. 18 A recent study in ref 19 in Southern Benin also revealed that D. vertebratus was the predominant species constituting 65% of the 17,665 Tephritid adults observed. Zeugodacus cucurbitae prefers watermelon, pumpkin and cucumber and can cause up to 100% loss in an unprotected crop.…”
Section: ■ Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To obtain high DNA quality, the heads of the parasitoids were excised before extraction according to the protocol of Livak, [ 45 ]. For the polymerase chain reaction (PCR) amplification, a Master Mix solution was prepared by mixing the barcoding primers LCO1490 (5′GGTCAACAAATCATAAAGATATTGG3′), and HCO2198 (5′TAAACTTCAGGGTGACCAAAAAATCA) for arthropods identification [ 46 ], DDH2O and hot start. Each sample was prepared with a 48 µL master mix solution in a PCR tube and 2 µL of DNA was added to the solution.…”
Section: Methodsmentioning
confidence: 99%
“…The tomato production system was also recorded as either an open field or greenhouse/screen house production. Additionally, an average number of N. tenuis per kilogram of tomato leaves were estimated and four classes were obtained for this variable 0 = absence of N. tenuis , [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] = low-level presence of N. tenuis , [ 50 ,…”
Section: Methodsmentioning
confidence: 99%